(untitled) (Emancipação, 2025)
The objectives of this article are to highlight the trajectory of the associated family farmers inserted in the National School Feeding Program (PNAE) and to verify the role played by the program in the socioeconomic conditions and autonomy of these women. This is a case study carried out in a community association in a municipality of the Recôncavo region of Bahia. Ten family farmers were interviewed, organized in an experience highlighted by the results achieved by the collective. The research revealed that the situation of social vulnerability still persists, the division of labor in the domestic environment is not equitable and the PNAE is the main tool for the flow of production. In addition, we found that associative participation constituted a formative space to unveil the inequalities experienced and, to some extent, an instrument for economic autonomy.